Is it ethical for health workers to strike? Issues from the 2001 QECH general hospital strike - Mfutso-Bengu, Joseph (Malawi Medical Journal, 2002)
Between 5th and 19th October 2001, a general strike in which virtually all workers at the Queen Elizabeth Central Hospital (QECH) were involved was effected. Hospital workers' grievances included low remuneration and poor work environment. The strike resulted in the virtual closure of the QECH, as the 1500-bed hospital was maintained less than a hundred in-patients. The outpatient department was closed. Patients that were still in hospital were being cared for by volunteer workers who included; the Red Cross, medical and nursing students and their lecturers. The two-week strike at QECH has left an almost indelible mark in as far as tertiary level health care delivery in Malawi is concerned. We report on the conduct of the hospital workers strike and discuss ethical issues in the light of the socio-political context of Malawi. While many people suggest that damage has definitely been done and felt, the ethical issues involved remain contentious as ever.